Perception of Risk Among Aesthetic Plastic Surgeons. (16th March 2021) - Sherif, Rami D; Lisiecki, Jeffrey; Gilman, Robert H
Abstract: Background: With continuous innovation in plastic surgery, new procedures are constantly being introduced. A number of these procedures are generally safe but have the potential for rare yet serious complications. Many surgeons steer clear of these procedures due to safety concerns. Objectives: The aim of this paper was to survey the membership of The Aesthetic Society to elicit perception of risk of several novel or less mainstream procedures. Methods: A 24-item survey was sent out to members of The Aesthetic Society. The survey focused on surgeon experience and attitude towards 3 procedures: filler rhinoplasty, gluteal augmentation with fat grafting, and submandibular gland excision. Results: In total, 189 completed surveys were returned. Of the responders, 50%, 49%, and 89% of surgeons said they do not perform filler rhinoplasty, gluteal augmentation with fat grafting, or submandibular gland excision in their practices, respectively. The majority of those who do not perform the procedures selected "danger to the patient" as the primary concern for each of the 3 procedures. Surgeons overwhelmingly reported not learning these procedures in training. Additionally, surgeons perceive the risks of more common procedures such as abdominoplasty and breast augmentation-mastopexy to be significantly lower and more acceptable than those of the studied procedures. Conclusions: When comparing the perceived complication rates with data published in the literature, particularly when looking at rates of serious or life-threatening complications, plastic surgeons overestimate the risks of procedures with which they are less familiar. This perception of risk, accompanied by the lack of exposure to novel techniques in training, may contribute to surgeons avoiding these procedures.